1987
DOI: 10.1002/jso.2930340113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionizing radiation on the primate pancreas: An endocrine and morphologic study

Abstract: In this study we evaluated the endocrine, biochemical, and haematological derangements as well as pancreatic and histological changes of the bonemarrow in the primate following external fractionated subtotal marrow irradiation without bonemarrow reconstitution. The irradiation was administered in preparation for pancreatic transplantation. Two groups of animals (ten in each group) received 800 rad (8 Gy) and 1,000 rad (10 Gy) respectively over 4 to 5 weeks. A maximum of 200 rads (2 Gy) were administered weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…Such degenerative changes that occurred in cytoplasm and organelles resulting in significant functions in each phase of radiation in order that cell could carry on its crucial activities would certainly decrease its process and distort its structure. Our results were in agreement with studies done on some animals tissues due to local irradiation or after high dose radiation (Gridley et al, 2001;Jagetia & Reddy, 2005;Santra & Mannal, 2009), and also some structural studies carried out on living organisms by some researchers (Barcellos-Hoff, 1998;Du Toit et al, 1987;Mansoub & Sarvestani, 2011;Somosy, 2000).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Such degenerative changes that occurred in cytoplasm and organelles resulting in significant functions in each phase of radiation in order that cell could carry on its crucial activities would certainly decrease its process and distort its structure. Our results were in agreement with studies done on some animals tissues due to local irradiation or after high dose radiation (Gridley et al, 2001;Jagetia & Reddy, 2005;Santra & Mannal, 2009), and also some structural studies carried out on living organisms by some researchers (Barcellos-Hoff, 1998;Du Toit et al, 1987;Mansoub & Sarvestani, 2011;Somosy, 2000).…”
Section: Discussionsupporting
confidence: 96%
“…Some acinar cells were severely damaged and the cytoplasm of cells showed open electron density. These data were corroborated by previous studies done on some animals by investigators (Arulselvan & Subramanian, 2007;Carr et al, 1992;Du Toit et al, 1987;Somosy, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…Short-term studies in baboons have shown morphologic changes to the pancreas and necrosis of pancreatic islet cells and acinar tissue (5). Pancreatic atrophy and exocrine pancreatic insufficiency in response to irradiation have been reported in dog models (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…High-dose whole-body irradiation (WBI) (8– 10 Gy cumulatively) injures beta cells and impairs insulin responses to glucose challenge in monkeys in the short term (5), however, less is known about the effects on the important muscle, liver and fat tissues that are involved in glucose disposal (6), production and inflammation, respectively. In the current study, we show the characteristics of a nonhuman primate cohort of monkeys that had been exposed to high-dose radiation 5–9 years earlier and compare these to age-matched nonirradiated monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, animal studies show that pancreatic radiation results in degranulation, vacuolisation, mitochondrial destruction, and impaired insulin secretion. 5, 6 However, additional functional damage is probably necessary for diabetes to develop. Otherwise, we would expect diabetes to occur in childhood, rather than young adulthood, that the risk would not plateau at 20–29 Gy, and that there would be a preponderance of type 1 diabetes.…”
mentioning
confidence: 99%